2011
DOI: 10.1038/nature10507
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage skewing by Phd2 haplodeficiency prevents ischaemia by inducing arteriogenesis

Abstract: PHD2 serves as an oxygen sensor that rescues blood supply by regulating vessel formation and shape in case of oxygen shortage1–5. However, it is unknown whether PHD2 can influence arteriogenesis. Here we studied the role of PHD2 in collateral artery growth by using hindlimb ischaemia as a model, a process that compensates for the lack of blood flow in case of major arterial occlusion6–8. We show that Phd2 (also known as Egln1) haplodeficient (Phd2+/−) mice displayed preformed collateral arteries that preserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
247
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 262 publications
(266 citation statements)
references
References 34 publications
10
247
2
4
Order By: Relevance
“…While our understanding of the role of HIF hydroxylases in the regulation of immune cell function is far from complete, recent studies investigating individual HIF hydroxylase isoforms in discreet immune and epithelial cell subtypes have identified isoform-specific roles (80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Notably, these phenotypes are not fully accounted for by downstream HIF-dependent effects, further supporting the existence of alternative hydroxylase-regulated pathways such as NF-κB in immune cells.…”
Section: Regulation Of Immune Cell Function By Phdsmentioning
confidence: 99%
“…While our understanding of the role of HIF hydroxylases in the regulation of immune cell function is far from complete, recent studies investigating individual HIF hydroxylase isoforms in discreet immune and epithelial cell subtypes have identified isoform-specific roles (80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Notably, these phenotypes are not fully accounted for by downstream HIF-dependent effects, further supporting the existence of alternative hydroxylase-regulated pathways such as NF-κB in immune cells.…”
Section: Regulation Of Immune Cell Function By Phdsmentioning
confidence: 99%
“…4A, 4B). However, it has still remained controversial regarding the role of NF-kB in macrophage differentiation, as someone supported the M1-prone effect of NF-kB, whereas others argued that NF-kB was equally important in priming M1 or M2 gene transcription or even had a negative effect on M1 macrophage development (32)(33)(34). We thus turned to other major signaling pathways such as MAPKs, which prove to play an essential role in mediating inflammatory response upon TLR engagement.…”
Section: Jnk Is Selectively Induced By Mir-127 To Skew the Macrophagementioning
confidence: 99%
“…Subsequent studies revealed that the mechanism by which hypoxia leads to activation of NF-kB is also largely dependent upon altered HIF-hydroxylase activity. [57][58][59] Hydroxylase Inhibitors in Models of IBD As outlined above, hydroxylases are key oxygen sensors, which confer hypoxic sensitivity to transcriptional regulators including HIF and NF-kB, both of which are protective against colitis when activated in intestinal epithelial cells. As HIF and NF-kB are key regulators of both immune and inflammatory processes 35,37 it was initially proposed that pharmacologic hydroxylase inhibition, leading to enhanced HIF and NF-kB activity may be of therapeutic benefit in chronic inflammatory conditions such as IBD.…”
Section: Hydroxylases As Intracellular Oxygen Sensorsmentioning
confidence: 99%